The reciprocal regulation of stress hormones and GABAA receptors - Mody, Istvan; Maguire, Jamie (Frontiers in Cellular Neuroscience, 2012)
Stress-derived steroid hormones regulate the expression and function of GABAA receptors (GABAARs). Changes in GABAAR subunit expression have been demonstrated under conditions of altered steroid hormone levels, such as stress, as well as following exogenous steroid hormone administration. In addition to the effects of stress-derived steroid hormones on GABAAR subunit expression, stress hormones can also be metabolized to neuroactive derivatives which can alter the function of GABAARs. Neurosteroids allosterically modulate GABAARs at concentrations comparable to those during stress. In addition to the actions of stress-derived steroid hormones on GABAARs, GABAARs reciprocally regulate the production of stress hormones. The stress response is mediated by the hypothalamic-pituitary-adrenal (HPA) axis, the activity of which is governed by corticotropin releasing hormone (CRH) neurons. The activity of CRH neurons is largely controlled by robust GABAergic inhibition. Recently, it has been demonstrated that CRH neurons are regulated by neurosteroid-sensitive, GABAAR δ subunit-containing receptors representing a novel feedback mechanism onto the HPA axis. Further, it has been demonstrated that neurosteroidogenesis and neurosteroid actions on GABAAR δ subunit-containing receptors on CRH neurons are necessary to mount the physiological response to stress. Here we review the literature describing the effects of steroid hormones on GABAARs as well as the importance of GABAARs in regulating the production of steroid hormones. This review incorporates what we currently know about changes in GABAARs following stress and the role in HPA axis regulation.